Prevalence of dental disorders among people with mental illness: An umbrella review. (August 2022) - Choi, Jisu; Price, Josh; Ryder, Samuel; Siskind, Dan; Solmi, Marco; Kisely, Steve
Objective: Psychiatric patients have increased rates of comorbid physical illness. There are less data on dental disease, especially decay, despite risk factors including lifestyle and psychotropic side effects such as xerostomia. We therefore undertook an umbrella review of all meta-analyses on the association between mental illness and oral health. Methods: We searched PubMed, MEDLINE, PsycINFO, the Cochrane Central Register of Controlled Trials, Embase and CINAHL. Articles were independently assessed. Outcomes were caries, periodontal disease, erosion, and partial or total tooth loss (edentulism), measured where possible with standardised measures such as the mean number of decayed, missing and filled teeth or surfaces. Quality was assessed in line with National Institutes of Health guidelines. Results: We identified 11 meta-analyses. The most information and strongest association was between dental decay and severe mental illness or substance use, as well as erosion and eating disorders. Depressive, anxiety and eating disorders were also associated with caries, but the datasets were small. People with severe mental illness had nearly three times the odds of having lost all their teeth than the general community (odds ratio = 2.81, 95% confidence interval = [1.73, 4.57]) and those with depression between 1.17 and 1.32. Findings for periodontal disease were more equivocal, possibly because of study heterogeneity. Conclusion: Mental health clinicians should screen for oral diseases when treating those with mental illness and facilitate referral to affordable dental clinics when indicated. Prevention should be a priority, including the promotion of dental care, as well as the management of xerostomia when psychopharmacologic agents are prescribed.